Enhancing Early Childhood Cognitive Skills Through Patterned Meronce Activities with Loose Parts - Dhiaulhaq, Mudrikah; Utami, Tri; Nabila Akifah Noor, Ayu (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
This study aims to improve cognitive abilities through patterned beading activities using loose parts in children aged 4-5 years. This research employs Classroom Action Research (CAR). The study was conducted in two cycles, each comprising four stages: planning, implementation, observation, and reflection. Data collection techniques used in this research include observation, interviews, performance assessments, and documentation. The results show that learning activities aimed at enhancing cognitive abilities through patterned beading with loose parts can effectively improve cognitive skills in recognizing patterns, particularly ABC-ABC patterns. The improvement is evident as the pre-cycle activities showed that the percentage of pattern recognition skills in the BSH and BSB categories was only 14.28%. In Cycle I, this increased to 50% in the BSH and BSB categories. Subsequently, in Cycle II, cognitive abilities in pattern recognition within the BSH and BSB categories further increased to 78.57%. These findings imply that incorporating loose parts in patterned beading activities can be a valuable strategy in early childhood education to enhance cognitive development.┬á┬á